Paraphrastic and non-paraphrastic reformulation and discourse ethos in academic writing in Spanish. Contrasts between specialized and advanced writing - Negroni, María Marta García (2009)
The subject of this article is paraphrastic reformulation, non-paraphrastic reformulation and discourse ethos and its traces in academic writing in Spanish. It analyzes the use of connective devices and discourse markers in texts written by specialists (discourse linguists) and texts written by graduation students in this area.